2009
DOI: 10.1002/smi.1272
|View full text |Cite
|
Sign up to set email alerts
|

Chewing gum, stress and health

Abstract: Hollingworth described chewing gum as ‘a technique of relaxation’. Recent research has examined this issue and there is evidence that chewing gum can prevent the adverse effects of acute stress. There are also plausible biological mechanisms that could explain such effects. It is now important to examine chewing gum and chronic stress and the present study involved a survey of this topic. The survey covered the ‘stress process’, collecting data on exposure to stressful events, levels of perceived stress and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 23 publications
5
26
0
Order By: Relevance
“…Furthermore, Smith's (2009c) survey data corroborate the self-rated data of Scholey et al, such that gum chewers (compared to non-chewers) reported significantly lower levels of extreme work stress, life stress, lifetime instances of high blood pressure, and lifetime incidences of high cholesterol.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, Smith's (2009c) survey data corroborate the self-rated data of Scholey et al, such that gum chewers (compared to non-chewers) reported significantly lower levels of extreme work stress, life stress, lifetime instances of high blood pressure, and lifetime incidences of high cholesterol.…”
Section: Introductionsupporting
confidence: 81%
“…Notwithstanding this analysis, sessions were longer in the Scholey et al study indicating that the effects of gum on stress may be limited to more prolonged instances of stress (e.g. see the survey examination of chronic stress by Smith, 2009c). Furthermore, some evidence of asymmetric transfer was found for contentedness and alertness.…”
mentioning
confidence: 91%
“…All of these reports include personality and individual difference variables as important components in the prediction and understanding of stress-and health-related outcomes and behaviour. The research reported here adopts diverse personality traits and trait-like constructs ranging from constructs from the fi vefactor model (Smith, 2009) to dispositional coping strategies (Chen, Siu, Cooper, & Phillips, 2009;Karademas, Karamvakalis, & Zarogiannos, 2009;Kozora, Ellison, & West, 2009). Many have included individual differences in demographic characteristics as important moderating factors or covariates (Galanakis, Stalikas, Kallia, Karagianni, & Karela, 2009;Karademas et al, 2009;Smith, 2009;Su, Weng, Tsang, & Wu, 2009).…”
Section: Personality and Individual Differences: Important Consideratmentioning
confidence: 99%
“…The research reported here adopts diverse personality traits and trait-like constructs ranging from constructs from the fi vefactor model (Smith, 2009) to dispositional coping strategies (Chen, Siu, Cooper, & Phillips, 2009;Karademas, Karamvakalis, & Zarogiannos, 2009;Kozora, Ellison, & West, 2009). Many have included individual differences in demographic characteristics as important moderating factors or covariates (Galanakis, Stalikas, Kallia, Karagianni, & Karela, 2009;Karademas et al, 2009;Smith, 2009;Su, Weng, Tsang, & Wu, 2009). There are also diverse and innovative methodological treatment of these variables including interactions between traits/individual differences and environmental/situational factors (Galanakis et al, 2009;Kunst, Bogaerts, & Winkel, 2009;Vaske, Beaver, Wright, Boisvert, & Makarios, 2009) and mediation effects (Karademas et al, 2009).…”
Section: Personality and Individual Differences: Important Consideratmentioning
confidence: 99%
See 1 more Smart Citation